Quo vadis Patria Gaucha? Uruguayan pathways of land use change - Säumel, Ina; Alvarez, Jorge; Ramírez, Leonardo R.; Barra, Marcos (Frontiers in Sustainable Food Systems, 2023)
South American grasslands, socio-ecological systems used heavily for a long time, are currently experiencing dramatic land-use changes due to implementation of large-scale afforestation and agro-industrial cash crops. Applying the conceptual framework of “Multifunctional and sustainable productive landscapes” to Uruguay, we explored the impacts on rural ecosystems and communities based on a long-term monitoring network by assessing species richness of plant and terrestrial arthropods and socio-economic data from national census. We found that silvi- and agricultural industry established mainly at the expense of extensively grazed grasslands and local family farms with traditional techniques, accompanied by a deregulation of the rural labor market, depopulation and aging of rural society. Governmental nature protection efforts increase the native forest cover and establish nature protection areas focusing mainly on forests. We also discuss pathways of land-use change in recent decades and related discourses of local stakeholders.